Artistic processing for the phenomenon of epidemiological foresight in the cinematic film (Al-Academy, 2023)
The artistic processing of the phenomenon of epidemiological foresight are among the important topics that cinematic films deal with greatly, as they led to a wide discussion about the ability of cinema to penetrate the minds of the recipients, understand what is inside them, and instill new ideas and concepts in them. The aim of foresight isn't to predict, but it is a scientific skill that aims to know the future trends of human life, and in cinematic films, these trends will affect all characters and events within the film, the research aims to shed light on the phenomenon of epidemiological foresight in cinematic films through the movie (Contagion), as well as introducing the concept of foresight, its methods and approaches, the research problem was represented by the following question: (What are the artistic processing for the phenomenon of epidemiological foresight in the cinematic film), while the theoretical framework included two sections: the first: a general introduction to the concept of foreseeing the future, and the second: the representations of epidemiological foresight in the cinematic film, while The research procedures have been taken from the descriptive analytical approach to the research, and the research ended with the results, conclusions and recommendations.